SIMULASI PEMBANGUNAN JARINGAN MOBILE DENGAN SRSLTE DAN OAI - Moch. Fahru Moch. Fahru Rizal; Prajna Deshanta Ibnugraha; Sandy Krisna Mukti; Malik Abdul Aziz (Indonesia Journal on Computing (Indo-JC), 2024)
Open Air Interface is a telecommunications infrastructure development platform that aims to create an open source 4G/5G telecommunications network. This technology can replace commercial 4G/5G network infrastructure and or interconnect with existing 4G/5G cellular networks. This study aims to create test-beds of 4G OAI and srsLTE in a limited non-commercial scope, using USRP B205-mini and B210 which runs 4G standard cellular services using a single-site scheme. The results of srsLTE and OAI integration have adequate performance in power of -32.6 dBm and a Power to Signal Ratio of 19.54 dB.